Increasing the Growth and Yield of Local Rice Varieties and Improving Soil Chemical Properties in Peatlands with Dolomite Application - Sari Susanti; Meli Roslianti (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Rice is a staple food crop for many people. However, rice production has been declining annually. If this decline continues, it could lead to a food crisis in Indonesia. The expansion of non-agricultural development has left the remaining agricultural land less fertile, particularly peat soils. This study was conducted on peatland in Tanah Putih District, Rokan Hilir Regency, Riau Province. A randomized complete block design (RCBD) with two factors was used. The first factor was dolomite lime dose at four levels: 0, 5, 10, and 15 tons per hectare. The second factor was rice variety, consisting of three levels: Inpari 32, Caredek, and Rotan. It resulted in 12 treatment combinations, each with three replications, for a total of 36 experimental units. Data were analyzed using ANOVA at the 5% significance level. Treatments showing significant differences were further analyzed using Duncan's New Multiple Range Test (DNMRT) at the 5% level. The results showed that the Caredek variety had the highest values for total tiller number, productive tiller number, and 1000-grain weight. The Inpari variety performed best in plant height, number of grains per panicle, and harvest age. However, dolomite application had no significant effect on any of the observed parameters. The study concluded that the Caredek variety is more adaptable to peat soils than the local Rotan variety.